Análisis de la superficie de resinas flexibles de poliamidas y resinas de metacrilato por microscopía electrónica de barrido - Gregorutti, Ricardo Walter (2017)
Polyamide and methacrylate based resins are currently used to elaborate removable dentures. These prostheses are supported by the mucosa of the residual mucous alveolar membrane, whereby the surface is of significant importance. Surface irregularities such as pores, folds and cracks can lead to the development and growth of colonies of microorganisms that give rise to inflammatory processes. Observation by scanning electron microscopy showed discontinuities at the surface of the polyamides between 4 and 20 μm and folds. In the case of the methacrylate resin, its surface showed signs of trapped air in the form of bubbles, some of which are exploited. It is estimated that these defects occurred during the casting process of the piece.